HUBUNGAN ANTARA KESIAPAN MENTAL DENGAN MOTIVASI BELAJAR PADA MATA PELAJARAN BIOLOGI - Tri Sutasmi Nirwan; Muh Rapi; Muchlisah Muchlisah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This study discusses the relationship of mental readiness with motivation to learn for Biology lesson of Learners at SMA Negeri 1 West Bajeng Gowa. This Research aims to review the readiness view of mind of the Learners which follow the subjects of Biology in SMA Negeri 1 West Bajeng Gowa, and to know the Relationship between mental readiness and motivation to learn on the subjects of Biology for the students of SMA Negeri 1 West Bajeng Gowa. This type of research is correlational . This research was held in SMA Negeri 1 West Bajeng, Gowa. The research sample is 156 people students. The analysis technique used is the analysis of descriptive statistics and inferential statistical analysis.Results of descriptive statistics , mental readiness obtained average value of 79.69 in middle category, with percentage of 69.78 % . For motivation to learn obtained average value of 101,07 in middle category,with a percentage of 69.23 % . Thus , it can be concluded that the F count > F table ie 8.612 > 3.90 , then H0 rejected and Ha accepted, meaning that the hypothesis is accepted .There is a relationship between mental readiness and motivation to learn in the subjects of Biology on the students of SMA Negeri 1 West Bajeng Gowa with the correlation value ( R) of 0.418 ( included in the category of moderate correlation)